2021
DOI: 10.1111/sms.14087
|View full text |Cite
|
Sign up to set email alerts
|

Performance‐determining factors in biathlon prone shooting without physical stress

Abstract: This study investigated the most important factors determining biathlon prone shooting performance. Ten female and 16 male biathletes (age 19.9 ± 2.9 years) from the national teams of Finland and Vuokatti‐Ruka Sports Academy performed 6 × 5 biathlon prone shooting shots without physical stress under laboratory conditions. Shooting performance and multiple aiming point trajectory variables were measured together with an analysis of triggering force. Based on the aiming point trajectory data principal component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Precision shooting is often the back-bone of all shooting training with the goal to improve technical factors for accuracy and speed of preparation [ 6 ]. Technical factors such as stability of hold, shooting accuracy, triggering [ 39 ], minimal body sway and rifle movement [ 40 , 41 ] are all associated with better shooting performance. However, shooting performance has been shown to decrease with elevated physical intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Precision shooting is often the back-bone of all shooting training with the goal to improve technical factors for accuracy and speed of preparation [ 6 ]. Technical factors such as stability of hold, shooting accuracy, triggering [ 39 ], minimal body sway and rifle movement [ 40 , 41 ] are all associated with better shooting performance. However, shooting performance has been shown to decrease with elevated physical intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Reinkemeier et al (25) suggested that since the time to fire an air rifle and the time to perform a soft trigger pull in pistol shots is about 3 seconds, the evaluation period should be between 2 and 4 seconds. Köykkä et al (26) explained thatwithout taking the physical stress into account, biathlon prone shooting performance, stability of hold, aiming accuracy, trigger cleaning and trigger timing are the most important factors. In addition, it was stated that the variables defining trigger cleaning, aiming accuracy and trigger timing affect 80% of the mean firing performance.…”
Section: Discussionmentioning
confidence: 99%
“…This article uses an 8-week functional fitness training interventional trial. 4 Experiments were conducted from March to April 2020. This paper used the RPE subjective sensory scale and the Meto-exercise strength comparison table to monitor the training effect.…”
Section: Investigation Methodsmentioning
confidence: 99%